Effective business process management (BPM) software puts business people in control placing process design, execution and management into the hands of the people who use it. - Mills, Jeff
Finally, executives on the business side of management teams are asking for technology that can be delivered, modified and executed by business people. The promises of many enterprise application investments were never realized in large part due to the fact that the business side was disengaged from their IT investments, leading to large disconnects between expected capabilities and actual capabilities.